A Progress Review on Challenges and Strategies of Flexible Cu2ZnSn(S, Se)4 Solar Cells. Issue 4 (4th January 2023) - Xie, Weihao; Yan, Qiong; Sun, Quanzhen; Li, Yifan; Zhang, Caixia; Deng, Hui; Cheng, Shuying
Abstract : Flexible Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells have the advantages of nontoxicity and low cost, showing great commercial potential in wearable devices, indoor photovoltaics, and building‐integrated photovoltaics. Currently, the performances of flexible CZTSSe devices still faces a huge gap on the commercialization level. Herein, the development of flexible CZTSSe devices to provide the challenges is summarized and possible strategies are explored. During the past ten years of research, flexible CZTSSe devices' efficiency has increased to 11.19% through studies of flexible substrates, residual stress, deposition processes, and physics. However, the improvement of efficiency is facing large challenges in severe open‐circuit voltage loss and low fill factor. After solving the issues by the strategies of deep‐level defect passivation and interface optimization, the efficiency of flexible CZTSSe solar cells is expected to reach the commercial level. Abstract : Flexible Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells have the advantages of nontoxicity and low cost, showing great commercial potential. The device efficiency has increased to 11.19% through the studies of flexible substrates, residual stress, and deposition processes. The challenges are summarized and possible strategies from the development of flexible CZTSSe devices are explored, which is expected to realize commercial application.